The Rare Cases of Parotid Gland Arteriovenous Malformations - Gupta, Manish; Shrawan Nijhawan, Vijay; Kaur, Cynthia; Kaur, Sukhpreet; Gupta, Akanksha (Case Reports in Otolaryngology, 2021)
Arteriovenous malformation (AVM) results from errors in vascular development during embryogenesis; absent capillary beds lead to shunting directly from the arterial to venous circulation. Although it is common in the head and neck region, AVMs located in the parotid gland are quite rare. Here, we report two cases of arteriovenous malformation of the parotid gland that presented to our out-patient setup with swelling in the parotid region and were diagnosed as arteriovenous malformation on histopathological study after surgical resection.